Intensity Modulated Photocurrent Microspectrosopy for Next Generation Photovoltaics. Issue 9 (16th August 2022) - Laird, Jamie S.; Ravishankar, Sandheep; Rietwyk, Kevin J.; Mao, Wenxin; Bach, Udo; Smith, Trevor A.
Abstract: In this report, a large‐area laser beam induced current microscope that has been adapted to perform intensity modulated photocurrent spectroscopy (IMPS) in an imaging mode is described. Microscopy‐based IMPS method provides a spatial resolution of the frequency domain response of the solar cell, allowing correlation of the optoelectronic response with a particular interface, bulk material, specific transport layer, or transport parameter. The system is applied to study degradation effects in back‐contact perovskite cells where it is found to readily differentiate areas based on their markedly different frequency response. Using the diffusion‐recombination model, the IMPS response is modeled for a sandwich structure and extended for the special case of lateral diffusion in a back‐contact cell. In the low‐frequency limit, the model is used to calculate spatial maps of the carrier ambipolar diffusion length. The observed frequency response of IMPS images is then discussed. Abstract : A large‐area laser beam induced current microscope adapted to perform intensity modulated photocurrent spectroscopy in an imaging mode is introduced for the first time and applied to study the degradation of a back‐contact perovskite solar cell. Diffusion‐recombination modeling of the spatio‐frequency data allows the extraction of images for key device parameters such as the ambipolar diffusion length.